Synthesis of polymeric additives based on itaconic acid and their evaluation as pour point depressants for lube oil in relation to rheological flow properties - A.M. Al-Sabagh; M.W. Sabaa; G.R. Saad; T.T. Khidr; T.M. Khalil (Egyptian Journal of Petroleum)
Modification of the wax crystal habit practical interest during transportation processing of lube oil at low temperature. Various pour point depressant (PPD) additives can facilitate this modification by different mechanisms. Comb shaped polymer additives are known to depress the pour point of lube oil by providing different nucleation sites for the precipitation of wax. This paper describes performance based design, synthesis, characterization and evaluation of comb shaped polymeric additives. Alkyl itaconates were prepared by the esterification of itaconic acid with different saturated alcohols C16/C18/NAFOL 20+A (Cav = 20)/NAFOL 1822 B (Cav = 22). The four synthesized monomers were characterized and copolymerized with styrene in different molar ratios. All the products were characterized by infra-red (FTIR), Nuclear Magnetic Resonance (NMR) Spectroscopy and Gel permeation chromatography (GPC). Rheological properties of lube oil (with and without additives) were studied by Brookfield viscometer. In this study the additives based on itaconic acid were evaluated as good PPD and rheology modifiers.